Pengembangan Kapasitas dan Kualitas Pelayanan Administrasi Terpadu Paten pada Aparatur Pemerintahan Kelurahan Nyapah di Wilayah Kecamatan Walantaka - Katla Novriyani; Diana Romdhoningsih; Mohamad Ali; Refi Mulyadi; Bayu Tiansyah Putra; Juli Arianto; Siti Mahfudoh; Een Nuraeni; Chusnul Fauziah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
“Kelurahan” is a public administration area that is the spearhead of government, especially in the Walantaka District area and is obliged to fulfill the needs and rights of every citizen in the form of civil services available only at the Nyapah Village government office. In reality, the work unit is still not optimal in carrying out its duties and functions, especially in providing services to the community. The purpose of this community service is to provide information and education that can improve the quality of service of the Nyapah Village apparatus, by increasing the ability to master science and technology, so that the implementation of services to the community can reach the speed as possible easily and at low cost by prioritizing the interests and needs of the community. The method used is descriptive with a qualitative approach with data collection, both through interviews, observations, and documentation. This journal describes the Integrated Village Administration Service Development Model (PATEN) as part of digital public services and transparency to the community. The purpose of this digital public service survey is to provide convenience in the level of service satisfaction to the community carried out by the Nyapah Village apparatus.